2012
DOI: 10.1055/s-0032-1312860
|View full text |Cite
|
Sign up to set email alerts
|

Lung, Liver and Lymph Node Metastases in Follow-Up MSCT: Comprehensive Volumetric Assessment of Lesion Size Changes

Abstract: Superior precision and inter-rater variability of volumetric over manual measurement of lesion change over time was demonstrated in a whole body setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Nevertheless, the use of lymph node volumetry seems to be dependent on the tumor entity, since semiautomated lymph node volumetry did not have added value for the characterization of lymph nodes in patients with malignant melanomas (26). Especially for metric analysis, the role of semiautomated measurement is under current discussion, since a huge amount of data will have to be evaluated in the field of oncologic imaging (27). Regarding the assessment of SAD, long-axis diameter, and volume in patients with non-small cell lung cancer, Beyer et al showed no benefit to the use of semiautomated 3D measurements for differentiating between benign and malignant lymph node infiltration (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the use of lymph node volumetry seems to be dependent on the tumor entity, since semiautomated lymph node volumetry did not have added value for the characterization of lymph nodes in patients with malignant melanomas (26). Especially for metric analysis, the role of semiautomated measurement is under current discussion, since a huge amount of data will have to be evaluated in the field of oncologic imaging (27). Regarding the assessment of SAD, long-axis diameter, and volume in patients with non-small cell lung cancer, Beyer et al showed no benefit to the use of semiautomated 3D measurements for differentiating between benign and malignant lymph node infiltration (13).…”
Section: Discussionmentioning
confidence: 99%
“…The intra-observer variability of measurements (repeated measurement of the same tumor by the same observer) was not evaluated, because according to other published data in lung-nodule measurement, this was expected to be similar or even lower than the inter-observer variability [16,26]. Although the software can provide a structure based segmentation algorithm optimized for lymph nodes or for liver segmentation that has been tested for accuracy in previous publications [18,19,24], we did not include the measurement of pathological lymph nodes and/or metastasis in this study, despite the requirement from the guidelines (WHO or RECIST). The results of the present study warrant further evaluation within a prospective study design.…”
Section: Discussionmentioning
confidence: 99%
“…The reliability of semi-automatic volumetric analysis is subject to ongoing research. Studies comparing the interobserver and/or intraobserver variability between semi-automatic and manual volume measurements have shown comparable results, namely, a superiority of semi-automatic measurements, depending on entity and used modality (14)(15)(16)(17). Also, this method depends on detection of lesions following Gd-EOB-DTPA enhancement.…”
Section: Discussionmentioning
confidence: 99%